The World Trade Organization - Bohne, E. author. aut Link
XII, 228 p. 15 illus.
Keywords: This book is about how the WTO functions as a public organization. It analyzes and evaluates the WTO from a public administration perspective which is absent from the current debate on WTO reforms dominated by the traditional view that only nation states matter, not international organizations.